Hexacarbonyl (Trimethylsilyl Ethyne) Dicobalt as MOCVD Precursor for Thin Cobalt Layer Formation1. Issue 14 (15th August 2013) - Georgi, Colin; Hildebrandt, Alexander; Tuchscherer, André; Oswald, Steffen; Lang, Heinrich
Abstract The low melting Co0 source [Co2(CO)6(η2‐Me3SiC≡CH)] (3) was prepared as a precursor system for the metal‐organic chemical vapor deposition (MOCVD) of cobalt. The synthesis of 3 was realized by the reaction of trimethylsilyl acetylene (2) with dicobalt octacarbonyl (1) in n‐hexane at ambient temperature. Vapor pressure measurements and TG‐MS analysis were performed revealing the suitability of 3 in the CVD process. Cobalt layers formed in a vertical cold wall CVD reactor were characterized by SEM, EDX, and XPS. The appropriate metallic films consist of a mixture of cobalt and cobalt oxide.